The Threat of Crimes Related to Robbery During COVID-19 at Barangay 176 Bagong Silang Caloocan City: Vol. 3, No. 1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers determined that the COVID-19 pandemic impacted the crime rate in Barangay 176 Bagong Silangan, Caloocan City. The threat of robbery-related crimes during COVID-19 in Barangay 176 Bagong Silang Caloocan City was reported due to the barangay lockdown caused by the COVID-19 pandemic surge. This caused people to change how they live, which may have a big impact on the residents, triggering them psychologically, physiologically, and emotionally. There is also a current change in the crime rate, which has turned down and has lower rates since the pandemic restricted people from going outside, giving them less access to means of committing crimes.The researchers used a descriptive method to find information about existing conditions. They distributed survey questionnaires to residents and barangay officials of Barangay 176, Caloocan City. The questionnaires contained closed-ended questions pertinent to the crime concerning the pandemic, and every question had corresponding translations to avoid misconceptions.Most respondents agreed to elevate the number of workers, and most experienced intense security risks in apprehending violators. The study suggested conducting informative programs like seminars, which most agreed to.The study's findings addressed the main problem encountered by the local authorities. They provided for its resolution by having barangay officials' intensive combined efforts, conducting seminars, and livelihood programs to deepen society's awareness about crimes and their consequences so that the fewer motives they get, the less likely they are to commit a crime. Based on what the respondents stated, robbery is the highest form of taking someone's things, and it is also one of the most difficult problems in our society that leads to growing faster. However, because of the pandemic, based on our data in Barangay 176 Bagong Silang Caloocan City, residents and barangay officialsThe study's findings addressed the main problem encountered by the local authorities. They provided for its resolution by having barangay officials' intensive combined efforts, conducting seminars, and livelihood programs to deepen society's awareness about crimes and their consequences so that the fewer motives they get, the less likely they are to commit a crime. Based on what the respondents stated, robbery is the highest form of taking someone's things, and it is also one of the most difficult problems in our society that leads to growing faster. However, because of the pandemic, based on our data in Barangay 176 Bagong Silang Caloocan City, residents and barangay officials stated that it dropped every year, causing the safe place of their people. The barangay officials may add training for their staff to prevent the crime rate. The barangay officials may persuade the residents to join in community awareness on robbery programs so they can prevent crime in their surroundings.